Patterns of medicine use in patients of common respiratory diseases treated in the Department of Pediatrics of BSMMU Hospital (Bangladesh Journal of Physiology and Pharmacology, 2015)
The present study had attempted to evaluate the medicine use pattern in selected respiratory diseases treated in the Department of Pediatrics of Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital. An observational cross sectional study was conducted in the department of Pediatrics, Bangabandhu Sheikh Mujib Medical University (BSMMU) between January 2012 to June 2013. Retrospective prescribing data of sixty cases of bronchiolitis and childhood pneumonia and thirty cases of bronchial asthma was collected from the Record Room and reviewed for inclusion. Then the included treatment records were reviewed and appraised thoroughly. Information regarding patient profile, clinical diagnosis and detail information about medicine was documented in an audit form. Average number of medicine was 3.84, 4.31 and 4.47 in bronchial asthma, bronciholitis and pneumonia respectively and 4.28 for respiratory diseases. Generic prescribing was 12.46% for department of Pediatrics. Antimicrobials were used in 90.00, 96.66 and 100.00 percent cases of bronchial asthma, bronchiloitis and pneumonia respectively. In case of pneumonia, highest prescribed antimicrobial was Ceftriaxone. Intravenous and oral steroids were used in 63.33, 26.66 and 0.00 percent cases of bronchial asthma, bronchiloitis and pneumonia respectively. Wide variation was observed with medicine selection in different respiratory diseases treated in the department of Pediatrics of BSMMU. Appropriateness of prescribing cannot be ascertained by medicine use study only. It was revealed that lots of diversity was present in the treatment or selection of medicine. Detail study using newer and comprehensive method and indicators may provide better understanding about prescribing, which might be beneficial to formulate interventions. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22676 Bangladesh J Physiol Pharmacol 2014; 30(2):9-13